Genome editing and engineering : from TALENs, ZFNs and CRISPRs to molecular surgery - Appasani, Krishnarao (UK; Cambridge University Press, 2018)
"Genome Editing and Engineering From Talens, ZFNs and CRISPRs to Molecular Surgery Recent advances in genome editing techniques using endonucleases such as TALENs and CRISPRs, combined with genomic engineering technologies have opened up a wide range of opportunities from applications in basic disease biology research to potential new diagnostic tools and clinical applications This complete guide to endonuclease-based genomic engineering gives readers a thorough understanding of this rapidly expanding field. Chapters cover the discovery, basic science, and application of these techniques, focusing particularly on their potential application to the treatment of cancer, and cardiovascular and immunological disease. The final section discusses the legal and ethical issues which accompany the technology. Providing authoritative coverage of the potential that genome editing and engineer carry, this is an ideal reference for researchers and graduate students and those working in the biotechnology and pharmaceutical industries, as well as in a clinical setting"--
Includes bibliographical references and index.
Keywords: Gene Editing; Transcription Activator-Like Effector Nucleases; Zinc Fingers; Clustered Regularly Interspaced Short Palindromic Repeats